2020
DOI: 10.1108/bfj-04-2020-0351
|View full text |Cite
|
Sign up to set email alerts
|

Content analysis of food safety implications in online flour-handling recipes

Abstract: PurposeNumerous food recalls and outbreaks were associated with wheat flour in recent years. Few consumers are cognizant of food safety risks associated with raw flour. The purpose of this study is to evaluate the food safety information and flour-handling behaviors presented in popular food blog recipes and in YouTube videos using cookie, cookie dough and egg noodle recipes as examples.Design/methodology/approachEighty-five blog recipes and 146 videos were evaluated. Blog author and video host food-handling e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 34 publications
4
28
0
Order By: Relevance
“…Safe recipes), which was printed and is available in digital version on the web [5]. The importance of including food safety messages in cookbooks and in media sources that provide recipes, as food blogs, has been internationally recognised as a way to promote safe food practices in the domestic environment (Barrett and Feng, 2021; Morrison and Young, 2019; Levine et al , 2017; Maughan et al , 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Safe recipes), which was printed and is available in digital version on the web [5]. The importance of including food safety messages in cookbooks and in media sources that provide recipes, as food blogs, has been internationally recognised as a way to promote safe food practices in the domestic environment (Barrett and Feng, 2021; Morrison and Young, 2019; Levine et al , 2017; Maughan et al , 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The study concluded that YouTube videos encompass verbal instruction and symbolic behaviour that may influence food safety behaviours and suggest that the absence of positive behaviours or inclusion of negative food safety behaviour may unintentionally promote malpractices to viewers. Barrett and Feng (2021) conclude that exposing consumers to YouTube video recipes that promote malpractices may lead to a higher risk for foodborne illness amongst consumers.…”
Section: Inclusion Of Food Safety Information In Youtube Videosmentioning
confidence: 92%
“…To achieve a behavior change, consumers need reminders of recommended practices. Previous studies (9,56) showed that popular recipes often lack food safety messages. Guidelines for social media influencers and cooking show hosts can be developed, such as the "Safe Recipe Styleguide" by The Partnership for Food Safety Education (61).…”
Section: (49)mentioning
confidence: 99%